2023
DOI: 10.3390/s23031218
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Spatiotemporal Analysis of Human Gait Based on Data from Depth Sensors

Abstract: Gait analysis may serve various purposes related to health care, such as the estimation of elderly people’s risk of falling. This paper is devoted to gait analysis based on data from depth sensors which are suitable for use both at healthcare facilities and in monitoring systems dedicated to household environments. This paper is focused on the comparison of three methods for spatiotemporal gait analysis based on data from depth sensors, involving the analysis of the movement trajectories of the knees, feet, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Participants wore a variety of clothing material, with some wearing wide-leg trousers that could easily be a source of error. 19) Table 1 presents the background and gait parameters of the participants. The normality test results showed normal distributions of walking speed, cadence, walk ratio, FTT, hip flexion, and hip extension in men and FTT and hip flexion in women.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants wore a variety of clothing material, with some wearing wide-leg trousers that could easily be a source of error. 19) Table 1 presents the background and gait parameters of the participants. The normality test results showed normal distributions of walking speed, cadence, walk ratio, FTT, hip flexion, and hip extension in men and FTT and hip flexion in women.…”
Section: Resultsmentioning
confidence: 99%
“…The spatiotemporal parameters based on knee joint coordinates have been reported to have errors ranging 2.6%–4.4% for typical trousers and 3.4%–7.7% for wide-leg trousers and skirts. 19) which may affect the indices related to the knee joint coordinates. Third, errors could exist between the statistical distributions estimated by the resampling technique using the bootstrap method and the actual distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Another research study found that the accuracy of gait analysis results using the foot velocity method and knee distance method, based on Microsoft Kinect technology, is notably influenced by the subject’s clothing. However, the accuracy of the center height method was not affected by clothing [ 27 ].…”
Section: Introductionmentioning
confidence: 99%